2013
DOI: 10.1111/jocs.12060
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis after Mitral Valve Repair

Abstract: Hemolysis is a potential complication of mitral valve repair. We report a case of hemolytic anemia after mitral valve repair successfully treated with re-repair, and review the literature on reoperation after failure of mitral valve repair with associated hemolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Our finding that Hx prevents systolic dysfunction in an experimental model of intravascular hemolysis, such as in PHZ-treated mice, supports this view and conclusively proves a causative role for NHBH in left ventricular dysfunction associated to hemolytic disorders. Furthermore, Hx could be important in case of cardiac valve surgery, where mechanical forces and shear stress are significantly increased [51,52]. Consistently, hemolysis associated to high shear stress has been reported after mitral valve repair [51,52] and could contribute to heart failure in these patients.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our finding that Hx prevents systolic dysfunction in an experimental model of intravascular hemolysis, such as in PHZ-treated mice, supports this view and conclusively proves a causative role for NHBH in left ventricular dysfunction associated to hemolytic disorders. Furthermore, Hx could be important in case of cardiac valve surgery, where mechanical forces and shear stress are significantly increased [51,52]. Consistently, hemolysis associated to high shear stress has been reported after mitral valve repair [51,52] and could contribute to heart failure in these patients.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, Hx could be important in case of cardiac valve surgery, where mechanical forces and shear stress are significantly increased [51,52]. Consistently, hemolysis associated to high shear stress has been reported after mitral valve repair [51,52] and could contribute to heart failure in these patients.…”
Section: Discussionmentioning
confidence: 64%
“…Of these, the reports we chose fulfilled the following three conditions: a clear degree of MR jet as seen on Doppler echocardiography; a clear interval from initial operation to the appearance of hemolysis, and a clear oneto-one relation between the MR grade and the interval in the case series; and an absence of causes other than MR jet collision, including partial annuloplasty dehiscence, protruding paravalvular suture material, the whiplash motion of tendinous chords, or regurgitant jet collision with the pledget or atrial wall. We evaluated nine case reports and two case series of hemolysis caused by unendothelialization of the annuloplasty ring with or without MR jet collision as measured by echocardiography or reoperation (Table 3) [4,[12][13][14][15][16][17][18][19][20][21]. The cases of reoperation include seven reports and two series.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that mechanical damage to RBC occurred because of blood flow disturbance, with the rapid acceleration and deceleration of the regurgitant jet, and high shear stress on the RBC [6]. Other authors have also reported the hemolytic anemia as the potential complication of mitral valve repair [7,8].…”
Section: Discussionmentioning
confidence: 99%